Hubungan antara Locus of Control dan Persepsi Siswa tentang Pendidikan dengan Motivasi Belajar serta Implikasinya dalam Pelayanan Bimbingan dan Konseling - Mona Yulia Zulfa; Daharnis Daharnis; Syahniar Syahniar (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2017)
The background of this research was the lack of  student’s learning motivation. Locus of control and student’s perception about education became factors that can predict student’s learning motivation. This research is aimed to describe: (1) locus of control, (2) student’s perception about education, (3) learning motivation, and examine: (4) the relationship between locus of control with learning motivation, (5) the relationship between student’s perception about education with learning motivation, and (6) the relationship between locus of control and student’s perception about education with learning motivation. This research applied quantitative method with a descriptive correlational. The populations of this research were 623 students of SMA Pertiwi 1 Padang in grade X and XI and the samples were 243 students, that were chosen by using proportional stratified random sampling technique. The instrument of the research was a model likert scale. The implication of this research can be made as a need assessment to make a program of guidance dan counseling service in SMA Pertiwi 1 Padang.